Free communes: An idea that neither dies nor catches on - Christensen, Jørgen Grønnegård (Politica, 2022)
The idea of the free communes was born in the 1980s and has been with us ever since. Government upon government has launched its own version of a world where local governments achieved more self-governance. This essay takes stock of the experience with free commune experiments in the Nordic countries. It concludes, not without a certain regret, that local governments are able to manage their own affairs, but they are not allowed to do it. Slightly acrimoniously, the essay reaches double conclusion: removing regulations is a popular program but it is impossible in practice, and the general trust in others that was the mainstay of one the more recent experiments does not survive the encounter with the everyday life of national politics.